DEFINING OF PHYSICAL-CHEMICAL PARAMETERS OF KRENA RIVER AS THE POLLUTER OF ERENIKU RIVER - Maloku, Faton; Haxhibeqiri, Burim (European Scientific Journal, ESJ, 2014)
The Krena river based on its length has bigger flow than Llukaci river, and both of them spillat Ereniku river. The purpose of this study is to provide details on the quality of the waterof Krena river and its flow to the Ereniku river. The study and monitoring performed in of this paper annual period january-december 2011gives its physical-chemical results as:Iron,Manganese,nitrites,nitrates,Aluminium,phosphate,consumption of Potassium permanganate,dissolved Oxygen,water temperature,air temperature,pH value etc.Water samples were taken in polyethylene bottles of 500 ml, which initially are well cleaned.Some of parameters were measured at the location of the taken sample, since other analyzes were sent immediately to the laboratory and analyzes were made,based on pH value, conductometric,turbidymetric, spectro photometric etc. The given results show the quality of the pollution of Krena river as result of discharge of pollutants , municipal and industrial.